ANALISA PERBANDINGAN WAKTU PENJADWALAN PROYEK DENGAN METODE CPM (CRITICAL PATH METHOD) DAN PDM (PRECEDENCE DIAGRAM METHOD) (Studi Kasus : Rehabilitasi dan Renovasi Sarana Prasarana SD Negeri Waemasing, Kec. Waesama, Kab. Buru Selatan) - Gabriel C. A. Lesbasa; Meyke Marantika; Nelda Maelissa; Rudi Serang (Journal Agregate, 2022)
Project delays are a highly unenviable condition. A school project in Waesama Sub-district, Buru Selatan Regency was delayed where 208 days of planning were not achieved, and were realized more than the plan. This study aims to distinguish the duration of the project using CPM and PDM on the project, as well as determine the optimal duration between the two methods. As well as obtaining critical jobs for CPM and PDM. CPM (Critical Path Method) is an AON (Activity on Node) method that only has one constrain, namely FS (Finish to Start). While PDM (Precedence Diagram Method) is an AON (Activity on Node) method that has 4 constrains FS (Finish to Start), SS (Start to Start), SF (Start to Finish), FF (Finish to Finish). The results of this comparative study found that there were differences in activities that were critical, there were also differences in duration after the use of these two methods. Where CPM produces a duration of 203 days, while PDM produces the most optimal duration of 200 days because it saves 8 days more than the duration of project planning. The use of PDM methods were more effective.